If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -1) + -2 = 4(n + -4) + -1(n + -11) Reorder the terms: 3(-1 + n) + -2 = 4(n + -4) + -1(n + -11) (-1 * 3 + n * 3) + -2 = 4(n + -4) + -1(n + -11) (-3 + 3n) + -2 = 4(n + -4) + -1(n + -11) Reorder the terms: -3 + -2 + 3n = 4(n + -4) + -1(n + -11) Combine like terms: -3 + -2 = -5 -5 + 3n = 4(n + -4) + -1(n + -11) Reorder the terms: -5 + 3n = 4(-4 + n) + -1(n + -11) -5 + 3n = (-4 * 4 + n * 4) + -1(n + -11) -5 + 3n = (-16 + 4n) + -1(n + -11) Reorder the terms: -5 + 3n = -16 + 4n + -1(-11 + n) -5 + 3n = -16 + 4n + (-11 * -1 + n * -1) -5 + 3n = -16 + 4n + (11 + -1n) Reorder the terms: -5 + 3n = -16 + 11 + 4n + -1n Combine like terms: -16 + 11 = -5 -5 + 3n = -5 + 4n + -1n Combine like terms: 4n + -1n = 3n -5 + 3n = -5 + 3n Add '5' to each side of the equation. -5 + 5 + 3n = -5 + 5 + 3n Combine like terms: -5 + 5 = 0 0 + 3n = -5 + 5 + 3n 3n = -5 + 5 + 3n Combine like terms: -5 + 5 = 0 3n = 0 + 3n 3n = 3n Add '-3n' to each side of the equation. 3n + -3n = 3n + -3n Combine like terms: 3n + -3n = 0 0 = 3n + -3n Combine like terms: 3n + -3n = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2(8q-1)+3(5q+6)= | | 12=2w+2 | | 10(x-5)=9(x+5) | | 9a-4+3a-33=23 | | 2(x-3)+4x=18 | | 5y-5=-35 | | 2(x-3)+4x=6.5 | | 7x-3x-8=24 | | 9y+y+8y+2y+5y= | | 2(x-3)=6.5 | | 3(2x-10)=6(x-10) | | 12x-3=4x+93 | | 3x^2=51x | | 25=4+3y | | 8b-11+3b=121 | | 284-2x=43x+19 | | -2(y-4)=12-y | | 25x^2-49=0 | | c^2=25 | | 5xn-3=32 | | 5(y+2)+3y=50 | | 3t+8t+3t+3t= | | 11-9x=87-37x | | -2w+5=26+w | | 8x=64 | | -5(x+37)= | | 15x^3+44x^2+11x-6=0 | | 6(x-5)=5(x+5) | | -90-9x=9x+18 | | -2x^2+128=0 | | 4x^2=26x-30 | | 11x-(6x+6)=19 |